Promising treatment biomarkers in asthma - Bonnesen, Barbara; Jensen, Jens-Ulrik S.; Mathioudakis, Alexander G.; Corlateanu, Alexandru; Sivapalan, Pradeesh (Frontiers in Drug Safety and Regulation, 2023)
Asthma is a highly heterogenous disease which researchers over time have attempted to classify into different phenotypes and endotypes to improve diagnosis, prognosis and treatment. Earlier classifications based on reaction to environmental allergens, age, sex and lung function have evolved, and today, the use of precision medicine guided by biomarkers offers new perspectives on asthma management. Identifying biomarkers that may reveal the underlying pathophysiology of the disease will help to select the patients who will benefit most from specific treatments. This review explores the classification of asthma phenotypes and focuses on the most recent advances in using biomarkers to guide treatment.